2017
DOI: 10.3906/vet-1607-26
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance profile of Enterococcus faecium andEnterococcus faecalis isolated from broiler cloacal samples

Abstract: Materials and methods Identification and isolation of enterococciTwo hundred and forty cloacal swab samples, which were collected in Cary-Blair transport medium from the slaughterhouses of three different integrated broiler companies in 2011 and 2012, were inoculated onto Slanetz and Bartley agar plates supplemented with vancomycin

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
5
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 16 publications
(23 reference statements)
5
5
2
Order By: Relevance
“…98% of the VRE isolates screened in this investigation were resistant to vancomycin and linezolid which were the drugs of choice for the treatment of enterococcal infections until the emergence of VREs worldwide. This finding is consistent with other reports worldwide [2, 4, 26, 30, 31, 33, 3639] although the proportions recovered varied from one study to another because of the samples source and the samples size. Moreover, the majority of the isolates in this study were also resistant to penicillin and erythromycin (94% and 82%, resp.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…98% of the VRE isolates screened in this investigation were resistant to vancomycin and linezolid which were the drugs of choice for the treatment of enterococcal infections until the emergence of VREs worldwide. This finding is consistent with other reports worldwide [2, 4, 26, 30, 31, 33, 3639] although the proportions recovered varied from one study to another because of the samples source and the samples size. Moreover, the majority of the isolates in this study were also resistant to penicillin and erythromycin (94% and 82%, resp.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the unavailability or scarcity of data from wholesale suppliers and the Department of Agriculture, Forestry, and Fisheries of South Africa makes it difficult to establish a link between antimicrobial usage in the feedlots and the observations made in this study. VREs were also detected in faecal samples of animal origin in other areas of South Africa [31, 36] and in other parts of the world [811, 30, 33, 3739] and these studies were consistent with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…However, a study conducted in Nigeria by Ngbede et al ( 2017 ) showed that E. faecium was the predominant (49%) species in chicken faeces. A similar result was also observed by Ali et al ( 2014 ) and Ünal, As˛kar and Yildirim ( 2017 ), with a prevalence of 66.0% and 33.6%, respectively. In these studies, E. faecalis was the second most prevalent species in chicken samples.…”
Section: Discussionsupporting
confidence: 89%
“…Our results were similar with the results of previous studies. In another study performed in our country, more than 80% of the enterococci were reported to be resistant to tetracycline and erythromycin; but Vancomycin resistance was not defined in any of the 235 Enterococcus isolates obtained in an animal study [13]. In a literature review, E. faecalis was reported to have a high resistance rate against erythromycin (67% resistance), gentamicin (65%), trimethoprim/sulfamethoxazole (54%), ciprofloxacin (51%) and oxacillin (49%), whereas nitrofurantoin (4% resistance) and teicoplanin (9%) were the most active agents against this species.…”
Section: Discussionmentioning
confidence: 89%